Ascorbic acid-loaded gliadin nanoparticles as a novel nutraceutical formulation. (November 2022) - Voci, Silvia; Gagliardi, Agnese; Fresta, Massimo; Cosco, Donato
Graphical abstract: Highlights: Gliadin-based nanoparticles were obtained using a commercial-grade raw material. Ascorbic acid was entrapped in order to obtain a nutraceutical formulation. The stability of AA was enhanced after its nanoencapsulation. The concentration of AA influenced its retention within gliadin nanoparticles. AA was released in a controlled manner under simulated digestive conditions. Abstract: Ascorbic acid (AA) is one of the foremost antioxidants. Unfortunately, its sensitivity to different external stimuli such as light, heat and oxygen are concrete limitations for its use. Various approaches have been investigated in order to circumvent this problem and enhance the stability of the active compound, besides promoting its use for different applications. In this investigation, AA was encapsulated in a vegetal protein-based matrix made up of gliadin, the prolamin obtained from wheat kernels, with the aim of proposing a novel nutraceutical formulation. The nanosystems were characterized by an average diameter of < 200 nm and a negative surface charge of ∼ −40 mV. The samples were not destabilized after incubation at different temperatures (up to 70 °C) or after the pasteurization procedure. Suitable stability was also observed in NaCl 100 mM, as well as after cryodesiccation when 10 % w/v of mannose was used. The gliadin nanoparticles showed the ability to retain high amounts of AA, promoting its prolonged release in PBS and under simulated gastrointestinal conditions. The nanosystems enhanced the antioxidant features of the compound as compared to its free form and preserved its chemical stability following UV exposition. The results demonstrate the potential application of the investigated nanoparticles as a novel nutraceutical formulation or as food fortificants.